Contestation of Customary and Islamic Law: Mangupa and Tuor in Horja Ritual at Tapanuli Muslim Community Wedding - Fatahuddin Aziz Siregar; Ibrahim Siregar; Suheri Sahputra Rangkuti (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2023)
This article discusses the change from custom to sharia with contestation of discourse between culture and religion in the horja ritual at the wedding of the Tapanuli Muslim community. Horja rituals that were initially based on local customs and traditions have undergone significant changes due to the influence of Islam. This article analyzes how the contestation between tradition and religion occurs and affects cultural identity. This type of research uses qualitative research with an ethnographic approach. This ethnographic approach is used to see how strong cultural and religious practices are attached to the wedding horja ritual of the Tapanuli Muslim community. This study found that cultural and religious contestation in the marriage horja ritual of the Tapanuli Muslim community targeted two cultural contents, namely, mangupa and the determination of tuor (offering). The authority of religious figures who managed to seize the influence of society to create a change in culture, namely from custom to sharia. These changes include replacing cultural practices, mantras, and symbols with Islamic practices and prayers and emphasizing Islamic religious teachings and practices in marriage ceremonies, mangupa, and tuor (offering). Contestation between indigenous and religious leaders arose to maintain control over culture and spiritual values. In addition, the role of Islamic religious figures has also penetrated the cultural domain. Artikel ini membahas perubahan adat ke syari’at menggunakan pendekatan kontestasi wacana antara budaya dan agama dalam ritual horja pada pernikahan masyarakat Muslim Tapanuli. Ritual horja yang awalnya didasarkan pada adat dan tradisi lokal telah mengalami perubahan signifikan akibat pengaruh agama Islam. Artikel ini menganalisis bagaimana kontestasi antara tradisi dan agama berlangsung dan memengaruhi identitas budaya. Jenis penelitian ini menggunakan penelitian kualitatif dengan pendekatan etnografi. Pendekatan ini digunakan untuk melihat seberapa kuat praktik kebudayaan dan agama melekat pada ritual horja pernikahan masyarakat muslim Tapanuli. Penelitian ini menemukan bahwa kontestasi budaya dan agama dalam ritual horja perkawinan masyarakat muslim Tapanuli menyasar dua konten kebudayaan, yaitu mangupa dan penetapan tuor (seserahan). Otoritas tokoh agama yang begitu kuat berhasil merebut pengaruh masyarakat sehingga menciptakan perubahan dalam budaya, yaitu dari adat ke syari’at. Perubahan ini mencakup penggantian praktik, mantra dan simbol budaya dengan praktik dan doa-doa Islam serta penekanan pada ajaran dan praktik agama Islam khususnya pada konten mangupa dan tuor dalam horja pernikahan. Kontestasi antara tokoh adat dan tokoh agama muncul dalam upaya mempertahankan kendali atas budaya dan ajaran agama. Selain itu, peran tokoh agama Islam juga sudah merambah domain kebudayaan.